A Study of Afghan Immigrants' Situation in Ataee's Koorsorkhi: A Story of Soul and War in the Discourse of Diaspora Studies - ayoob moradi; Ali Jamshidi (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
Theorists of diaspora studies have considered three different states for immigrants who live far from their ancestral homeland: the desire to return to one's original homeland, the attempt to make the new land one's home and considering homeland as a fluid conception. Iranian-Afghan writer Alieh Ataee has also addressed this issue in her latest work, Koorsorkhi: A Story of Soul and War (2021). The present descriptive- analytical paper examines characteristics of the immigrants in this collection, based on the three perspectives mentioned above. The results show that due to the existence of unresolved issues and problems in Afghanistan and the permanent political unrest, a small number of immigrants are willing to return to their homeland. In contrast, there is a greater number of immigrants who are completely disillusioned with their ancestral homeland and want to create a home in the new country. There is also a group who is caught in-between their original homeland and their new home, and this constant confusion has caused serious injury to their psyche. Koorsorkhi points to a new situation to which the paper refers as the "borderline identity", a situation in which the immigrant consciously chooses when to be considered as Afghan or Iranian, depending on the circumstances.